Enhancing efficiency and stability of perovskite solar cells via in situ incorporation of lead sulfide layer. Issue 14 (28th June 2021) - Zhang, Yue; Han, Yuxia; Xu, Yanting; Yu, Guanghui; Miao, Yu; Gao, CaiYan; Zhou, Xueqin; Song, YanLin; Jiang, Ke-Jian
Abstract : Surface defects of perovskite films were passivated by lead sulfide through in situ reaction with thioacetamide in solution, and the resultant perovskite solar cell exhibited a stable output efficiency of 21.22% with high stability. Abstract : The trap states at the surface and grain boundaries of perovskite films have a great influence on the photovoltaic performance and stability of perovskite solar cells (PSCs). Herein, lead sulfide (PbS) was introduced on the surface of perovskite films through in situ reaction with thioacetamide (TAA) in solution. With the PbS layer, the trap state density of the perovskite film was significantly reduced, and charge extraction efficiency was enhanced from perovskite to the external charge transport layer. In addition, it was found that the water-insoluble PbS layer could effectively protect the perovskite film from the moisture permeation. As a result, the perovskite solar cell exhibited a stable output efficiency of 22.04% with high stability.